(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In various fields, the precision of numerical data is crucial to ensure accurate results and reliable communication of findings. This paper provides a comprehensive overview of the rules and principles governing the use of significant digits during arithmetic operations. The discussion covers addition, subtraction, multiplication and division, emphasizing the importance of rounding results to maintain consistency with the least precise measurement involved. Examples from scientific research, engineering, finance and everyday life illustrate the application of significant digits. The guidelines presented aim to assist in ensuring the accuracy of computations, preserve measurement precision and facilitate clear reporting. Additionally, the challenges associated with significant digits, such as ambiguity with trailing zeros, mixed operations and instrument precision, are discussed. The paper concludes by reinforcing the critical role significant digits play in ensuring reliable numerical data across diverse applications.